Prediction of sulfuric acid dew point temperature on heat transfer fin surface. (5th April 2016) - Wang, Y.C.; Tang, G.H.
Highlights: Local sulfuric acid dew point on fin surface is predicted for the first time. Wall temperature, flue speed and fin effects on acid dew point are firstly studied. Sulfuric acid dew point is higher on windward and first row of fin surface. Novel types of fin surfaces can reduce sulfuric acid dew point temperature. Abstract: Sulfuric acid dew point temperature is an important parameter denoting the dew point corrosion. The sulfuric acid dew point temperature is calculated by considering both the vapor–liquid equilibrium effect and multi-component diffusion effect. In addition, the local distribution of acid dew point temperature on fin surface is numerically predicted for the first time. The influences of fuel type (sulfur content, water content and ash content), wall temperature, excess air ratio, flue gas inlet velocity, fly ash particle (size and quantity) and heat transfer fin structure on the sulfuric acid dew point temperature are discussed. The results show that different types of fuels (which differ in gas composition and combustion temperature) have a great impact on the sulfuric acid dew point temperature. The sulfuric acid dew point temperature decreases with the reduction of excess air ratio, the increasing of wall temperature, and the condensation of sulfuric acid vapor on ash particle surface. The sulfuric acid vapor condensates more seriously on the tube windward than on the leeward. The novel types of heat transfer fins with high heat transfer performance can also reduce the local sulfuric acid dew point temperature, and the maximum reduction of sulfuric acid dew point is 4.1 K between the novel fin surface and the original H-type fin surface.